Metodologia de modelagem de diferentes dissipadores de calor com resfriamento líquido em microcanais - Flores, Édson (Universidade do Vale do Rio dos Sinos, 2017)
This work has the objective of modeling different heat sinks with liquid cooling in microchannels. The proposal is the use of fluid dynamics software to analyze the thermal performance in different constructional geometries of microchannels. The software used to perform the CFD simulations was Ansys Fluent R . This work addresses the previous steps required for CFD simulation, highlighting the step of mesh generation for the simulations, involving mesh convergence study, simulation acceptance criteria and refining techniques at the liquid-solid interface, a procedure necessary for Modeling of heat transfer physics. The geometries studied were of rectangular section microchannels in parallel, microchannels of pinched structure and microchannels in fractal network of type H. A case study was also modeled in this work in which parallel microchannels were formed by walls of adhesive material In an aluminum block, in which the results obtained serve to aid in a stage of construction of an experimental prototype. In the study of the microchannels of rectangular section in parallel and microchannels of pinned structure, we varied the dimensional aspects seeking the best response of thermal performance, being expressed in terms of thermal resistance. The simulation of microchannels in fractal network H was performed for a qualitative comparison referring to the other geometries studied. A problem discussed in the course of this work was the need to change the laminar viscosity model to a turbulent viscosity model despite the velocity of the fluid inside the microchannels being low and expressing a low Reynolds number. Techniques for heat removal in microchannels can contribute decisively to the thermal management of a project, the lower energy used for cooling and the reduction of the dimensions of an end product. The geometries studied can be constructed in a metal layer of a metal core type printed circuit board, as well as being present in a one-chip silicon structure. The domain of thermal modeling techniques with fluid dynamics simulators presented in this paper can help in the search for technological solutions for micro-scale heat removal, reduce the need for prototype production, and consequently reduce costs.
Keywords: Microcanais; Simulação de dinâmica de fluidos; CFD; Microchannels; Fluid dynamics simulation; ACCNPQ::Engenharias::Engenharia Elétrica